2015
DOI: 10.1161/strokeaha.114.007006
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Simvastatin for Aneurysmal Subarachnoid Hemorrhage

Abstract: A lthough aneurysmal subarachnoid hemorrhage (SAH) accounts for only 3% to 5% of strokes, its profound consequences and unique window of intervention justify its classification as a separate entity.1 Early aneurysm occlusion, expert endovascular neurosurgery and microsurgery, and the use of oral nimodipine and neurointensive care are now standard treatment procedures. 2,3 Nevertheless, aneurysmal SAH is still associated with mortality after 1 month for half of all patients, whereas another quarter is left wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 33 publications
1
33
1
Order By: Relevance
“…The effects of statin in the prevention of cerebral vasospasm after SAH are still controversial. Some randomized trials showed a decrease in the incidence of vasospasm in the statin groups unlike in the control group, but other studies did not show a significant difference 1 6 8 11 15 16 17) . The result of a recent multicenter prospective study that compared patients treated with 40 mg of statin for 14 days with the control group showed no difference in the incidence of vasospasm and the clinical outcome 6) .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The effects of statin in the prevention of cerebral vasospasm after SAH are still controversial. Some randomized trials showed a decrease in the incidence of vasospasm in the statin groups unlike in the control group, but other studies did not show a significant difference 1 6 8 11 15 16 17) . The result of a recent multicenter prospective study that compared patients treated with 40 mg of statin for 14 days with the control group showed no difference in the incidence of vasospasm and the clinical outcome 6) .…”
Section: Discussionmentioning
confidence: 97%
“…The informed consent of either the patient or his or her next of kin was obtained. Previous studies showed that the short-term use of high-dose statin did not compromise safety 7 8 17) . Thus, we treated aneurysmal SAH patients with 80 mg, 40 mg, or 20 mg simvastatin (Simvastatin®; Yuhan Corporation, Seoul, Korea) for preventing cerebral vasospasm and retrospectively reviewed prospectively collected database.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The primary ordinal analysis of the mRS, adjusted for age and WFNS grade on admission, showed no benefit. In another study Wong et al compared low and high dose simvastatin, 40 vs. 80 mg. [25] The groups did not differ in the incidence of delayed ischemic deficits (27% versus 24%) or in the rate of favorable outcomes (mRS score 0–2) at 3 months (73% versus 72%). Taken together these data indicate that simvastatin likely does not improve functional outcome in SAH.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous clinical trials studied novel pharmaceutical treatments (i.e., nicardipine, tirilazad, statins, clazosentan, magnesium, etc.) against DCI, but oral nimodipine remains the only drug to improve neurological outcome in SAH patients [50,19,51,20,52]. Whether the lack of efficacy of these drugs originated from small sample sizes, insensitive outcome measures, insensitive pharmacological targets, or detrimental systemic effects is uncertain [53].…”
mentioning
confidence: 99%